A young, dusty, compact radio source within a Lyα halo - Barrio, F; Jarvis, M; Rawlings, S; Bauer, A; Croft, S; Hill, G; Manchado, A; McLure, R; Smith, D; Targett, T (Oxford University Press, 2008)
We report here on the discovery of a red quasar, J004929.4+351025.7 at a redshift of z = 2.48, situated within a large Lya emission-line halo. The radio spectral energy distribution implies that the radio jets were triggered < 10^4 years prior to the time at which the object is observed, suggesting that the jet triggering of the active galactic nucleus is recent. The loosely biconical structure of the emission-line halo suggests that it is ionised by photons emitted by the central quasar nucleus and that the central nucleus is obscured by a dusty torus with Av 3.0. The large spatial extent of the Lya halo relative to the radio emission means this could only have occurred if the radio jets emerged from an already established highly-accreting black hole. This suggests that the radio-jet triggering is delayed with respect to the onset of accretion activity on to the central supermassive black hole.